ANALYSIS OF SOLAR ENERGY POTENTIAL IN THE PT. SUMEDANG TELEVISI UTAMA BUILDING AS AN ALTERNATIVE ENERGY SOURCE - Tendy Ferdyansyah; Arnisa Stefanie (TEKNOKOM, 2023)
Indonesia is a tropical region with significant solar energy potential, where the average daily sunlight reaches 4.5 - 4.8 kWh/mÂ²/day. This makes solar energy one of the promising forms of renewable energy worthy of development. The instability of electricity supply from the national grid (PLN) is a prevalent issue across various regions. PT. Sumedang Televisi Utama (SMTV), a television broadcasting company, frequently encounters disruptions in TV broadcasts due to power supply issues originating from PLN. Hence, this research holds the urgency to explore alternatives that can provide electricity supply during interruptions in the PLN power distribution. The contribution of this study lies in the development of a practical and applicable Photovoltaic Solar Power Plant (PLTS) module. With the implementation of this module, it is anticipated that PT. Sumedang Televisi Utama (SMTV) and other entities can have a backup electricity supply source, mitigating the impact of power supply disturbances from PLN. Suggesions for further research include delving deeper into the efficiency and performance assessment of the designed PLTS module under various environmental conditions and weather patterns that are typical in Indonesia. Furthermore, subsequent research could focus on integrating a more effective energy storage system with the PLTS module, thereby maximizing solar energy utilization even during periods of limited sunlight. This endeavor would enhance the resilience and availability of alternative power supply during instances of disruptions in the national grid (PLN) distribution.